Safety of maximal cardiopulmonary exercise testing in individuals with sickle cell disease: a systematic review. Issue 13 (20th July 2021) - Smith, Kellsey N; Baynard, Tracy; Fischbach, Peter S; Hankins, Jane S; Hsu, Lewis L; Murphy, Peggy M; Ness, Kiri K; Radom-Aizik, Shlomit; Tang, Amy; Liem, Robert I
Abstract : Objective: We evaluated the safety of maximal cardiopulmonary exercise testing (CPET) in individuals with sickle cell disease (SCD). Maximal CPET using gas exchange analysis is the gold standard for measuring cardiopulmonary fitness in the laboratory, yet its safety in the SCD population is unclear. Design: Systematic review. Data sources: Systematic search of Medline (PubMed), EMBASE, Cochrane, ClinicalTrials.gov and professional society websites for all published studies and abstracts through December 2020. Eligibility criteria for selecting studies: Two reviewers independently extracted data of interest from studies that assessed safety outcomes of maximal CPET in children and adults with SCD. A modified version of the Newcastle-Ottawa Scale was used to assess for risk of bias in studies included. Results: In total, 24 studies met inclusion/exclusion criteria. Adverse events were reported separately or as part of study results in 36 (3.8%) of 939 participants with SCD undergoing maximal CPET in studies included. Most adverse events were related to transient ischaemic changes on ECG monitoring or oxygen desaturation during testing, which did not result in arrhythmias or other complications. Only 4 (0.43%) of 939 participants experienced pain events due to maximal CPET. Conclusion: Maximal CPET appears to be a safe testing modality in children and adults with SCD and can be used to better understand the physiological basis of reduced exercise capacity and guide exercise prescription in this population. Some studies did not focus on reporting adverse events related to exercise testing or failed to mention safety monitoring, which contributed to risk of bias.